An overview of learning discipline in secondary school students - Sesila Ina Harut; Sitti Anggraini (Cigarskruie: Journal of Educational and Islamic Research, 2023)
This study aims to determine the learning discipline of students at SMP Negeri Alok Maumere. Sampling using incidental sampling technique. Learners in this study amounted to 55 people. This type of research is a quantitative-descriptive approach. The results showed that the description of students' learning discipline was in the moderate category totaling 26 people, with a percentage of 50.9%, meaning that some students already had learning discipline. While some students do not have learning discipline, this can be seen from the indicators found, namely the indicator of being on time in learning which includes coming and going home on time, a mean of 21.25, an indicator of not leaving class, a mean of 19.84, an indicator of completing assignments according to a predetermined time and discipline in preparing learning equipment, a mean of 20.74. Based on the results of the t test on gender, it was found that there was no difference between men and women with a significance result of 0.126 (0.126> 0.05), which means that both men and women have the same opportunity to carry out learning discipline. Judging from the place of residence, namely living with parents with a higher mean test result of 64.5, which means that the role of parents is very important to support student learning discipline.